Comparison of sentinel lymph node biopsy guided by blue dye with or without indocyanine green in early breast cancer. Issue 8 (22nd May 2018) - Shen, Songjie; Xu, Qianqian; Zhou, Yidong; Mao, Feng; Guan, Jinghong; Sun, Qiang
Abstract : Background: There were limited data available for a head‐to‐head comparison of the identification rate and survival between the combined method of indocyanine green fluorescence and blue dye versus the traditional blue dye alone method for sentinel lymph node (SLN) biopsy. Methods: From January 2013 to December 2015, 523 eligible breast cancer patients were included in this nonrandomized prospective analysis. The identification rates, the number of SLNs identified, and the disease‐free survival (DFS) between the two mapping methods were compared. Results: The identification rate of SLNs was significantly higher with the combined method than that with the blue dye alone method (99.2% vs 93.3%, respectively; P  < 0.001). The average number of SLNs identified per patient in the combined method group was 3.7 ± 2.4, which was more than that in the blue dye alone group (3.2 ± 1.6; P  = 0.004). With a median follow‐up of 29 months, 0.5% patients in the combined group, and 1.3% patients in the blue dye group had axillary recurrences. The DFS between the two groups showed no significant difference ( P  = 0.161). Conclusion: The combined method achieved a higher identification rate and lower rate of axillary recurrence compared to the blue dye alone method.